2013
DOI: 10.5588/pha.13.0010
|View full text |Cite
|
Sign up to set email alerts
|

It's hard work, but it's worth it: the task of keeping children adherent to isoniazid preventive therapy

Abstract: HIV-infected children, previously paralysed postexposure IPT programmes have been enhanced through the introduction of IPT registers and the increased availability of single-drug dispersible paediatric isoniazid (INH) formulations.South Africa, an upper middle-income country, has a medium human development index, but it fi gures among the 22 countries with the highest burden of TB disease. 12 Although the South African National TB Programme (SANTP) has been recommending postexposure IPT for many years for chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Caregivers' refusal to medicate has been shown to be a significant barrier to providing children with IPT. [20] …”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caregivers' refusal to medicate has been shown to be a significant barrier to providing children with IPT. [20] …”
Section: Study Limitationsmentioning
confidence: 99%
“…[16] Qualitative studies in Cape Town have shown that barriers to a successful IPT programme included health systems issues, such as staff shortages and patient-and communityrelated factors, including poverty, stigma and parents' resistance to treatment. [20] The successful implementation of child contact screening and management is hampered by a variety of challenges and barriers unique to each setting. [7] Information regarding IPT services in the Eastern Cape and NMBHD is lacking, with no baseline data.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…4 What has been lacking, however, is operational research exploring the barriers to TB diagnosis, treatment and prevention among children. It is heartening to see this edition of Public Health Action dedicated to the topic, [5][6][7][8][9] and it is hoped that this will inspire others in this important fi eld of research.There are many areas that need urgent attention. These include the development and implementation of point-of-care diagnostics for children, new childfriendly drugs for children with drug-susceptible and drug-resistant tuberculosis, randomised controlled clinical trials to ensure optimal treatment for complicated cases such as TB meningitis, new short-course interventions to prevent TB and a new, effective vaccine.…”
mentioning
confidence: 99%
“…4 What has been lacking, however, is operational research exploring the barriers to TB diagnosis, treatment and prevention among children. It is heartening to see this edition of Public Health Action dedicated to the topic, [5][6][7][8][9] and it is hoped that this will inspire others in this important fi eld of research.…”
mentioning
confidence: 99%